2019
DOI: 10.1038/s41541-019-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of Zika neutralization assays by using the WHO International Standard for anti-Zika virus antibody

Abstract: During outbreaks of emerging viruses, such as the Zika outbreak in 2015–2016, speed and accuracy in detection of infection are critical factors to control the spread of the disease; often serological and diagnostic methods for emerging viruses are not well developed and validated. Thus, vaccines and treatments are difficult to evaluate due to the lack of comparable methods. In this study, we show how the 1st WHO International Standard for anti-Zika antibody was able to harmonize the neutralization titres of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(25 reference statements)
2
16
0
Order By: Relevance
“…Another study used our ZIKV and DENV RVPs for testing of longitudinal human serum samples following positive results by RT-PCR and ELISA, reporting the first cases of ZIKV-PLOS NEGLECTED TROPICAL DISEASES infected U.S. blood donors outside of states with areas of active transmission [27]. Moreover, our results are consistent with a multi-laboratory study that compared the reproducibility of our ZIKV RVPs to other methods of ZIKV detection in establishing World Health Organization standards for ZIKV neutralization assays across numerous serological samples and laboratories [49]. In this prior study, PRNT assays using the same serological samples across laboratories showed a wide divergence in neutralization titers, up to 100-fold different.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Another study used our ZIKV and DENV RVPs for testing of longitudinal human serum samples following positive results by RT-PCR and ELISA, reporting the first cases of ZIKV-PLOS NEGLECTED TROPICAL DISEASES infected U.S. blood donors outside of states with areas of active transmission [27]. Moreover, our results are consistent with a multi-laboratory study that compared the reproducibility of our ZIKV RVPs to other methods of ZIKV detection in establishing World Health Organization standards for ZIKV neutralization assays across numerous serological samples and laboratories [49]. In this prior study, PRNT assays using the same serological samples across laboratories showed a wide divergence in neutralization titers, up to 100-fold different.…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were also seen comparing the RVP assays performed in different laboratories. Our results are also consistent with an independently published paper that compared the reproducibility of our ZIKV RVPs to other methods of ZIKV detection, including PRNT, in the standardization of neutralization assays across numerous serological samples and laboratories [49].…”
Section: Zikv Rvps Can Be Used To Derive Reproducible Neutralization supporting
confidence: 90%
See 1 more Smart Citation
“…Antibody sourced for the study was a pool of polyclonal convalescent plasma obtained from two donors originating in the Dominican Republic, supplied by Boca Biolistics Ltd, Florida, USA. This material had been pre-prepared as an anti-Zika working reagent (NIBSC 16/ 320) whereby multiple lyophilised vials were reconstituted to derive a pool of convalescent plasma, characterised as part of a collaborative study of anti-Zika antibodies 23 . Results from this collaborative study assigned a value of 2756 IU/mL (95% confidence limits of 2003 to 3792 IU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Whilst there is strong evidence that anti-Zika immune sera may protect, the challenge of measuring the amount of antibody required in a robust comparative manner has prevented clear statements on how strong an anti-ZIKV response is required for vaccine success. Recently a reference material, the 1st WHO International Standard for anti-Asian lineage ZIKV antibody was established to harmonise measurement of these antibodies 23 . Here, we demonstrate that a human anti-Zika convalescent plasma pool calibrated as part of that study passively protected cynomolgus macaques (Macaca fascicularis) against challenge with South American-derived Asian lineage ZIKV.…”
Section: Introductionmentioning
confidence: 99%